The preference of Muslim young generation in using digital zakat payment: Evidence in Indonesia - Mohammad Nur Rianto Al Arif; Nofrianto; Muhammad Iqbal Fasa (Universitas Negeri Surabaya, 2023)
This study aims to analyze the behavior of digital zakat payments in Indonesian Muslim youth. This research is using multinomial logit by dividing three alternative zakat payment media, namely digital payment, cash, or using both media with 306 respondents. The research results show that perceived usefulness, ease of use, and risk affect intentions to use digital zakat payments. The other variables such as continuity and trust don’t have an impact on intention. Similar results were also obtained for intentions to pay zakat in cash. The implications of these results indicate that zakat management organizations must improve features on digital payment platforms to make it easier for people to pay zakat. Zakat management organizations must adapt to technological developments. This study offers new insight about the intention of muslim youth generation paying zakat through digital platform.